Pelaksanaan Program Kelas Budidaya Silvofishery Bagi Kelompok Pembudidaya Ikan di Kelurahan Degayu Kota Pekalongan - Heri Ariadi; Ashari Fahrurrozi; Farchan Mushaf Al Ramadhani (Journal of Community Development, 2024)
Silvofishery is an environmentally friendly fish farming concept that is starting to be developed in coastal areas. The aim of this service activity is to determine the level of understanding of coastal area communities regarding the application of the silvofishery cultivation model. The method used in this service is community education through an empowerment program which is carried out based on the level of active participation of participants. The results of the service reflection show that the level of knowledge of cultivators increased by 83% after the implementation of the cultivation class, as well as the knowledge of cultivators about the advantages and advantages of silvofishery also increased respectively by 58.33% and 50% after the implementation of the silvofishery cultivation class. Another impact of implementing this silvofishery cultivation class is that the farmers understand better the techniques for managing water quality in ponds. Farmers' knowledge of water quality management techniques in pond ecosystems increased by 58.33% from the original 0.00%. This means that the silvofishery cultivation class program is very effective and beneficial for fish farmers. Apart from that, the implementation of this cultivation class is quite educational and practical for disseminating the results of aquaculture engineering innovations. The conclusion from this service activity is that fish farmers on the Degayu coast, Pekalongan City tend to be very unfamiliar and do not understand the silvofishery cultivation model. From the implementation of this cultivation class, it turns out that it can have a significant influence on increasing the knowledge of the cultivating community about the silvofishery cultivation model from 15.25% to 89.33% by combining the concept of simplicity.